PENGEMBANGAN BAHAN AJAR BERBASIS E-BOOK MATEMATIKA MELALUI SOAL CERITA BERNUANSA ISLAMI DALAM MENINGKATKAN PEMAHAMAN KONSEP TINGKAT SD - Yulia Rahmawati; Muhammad Arie Firmansyah; Indriana Putri Galuh; Hani Nurbaiti (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
Research on the development of Islamic mathematic e-book as teaching materials at the elementary level is expected to help students in learning mathematics to improve students' conceptual understanding. Besides that, Islamic e-books are more effectively used in mathematics learning and become one of the innovations as a medium for learning mathematics. The research methodology uses the R & D method (ADDIE). This research was conducted at the SD IT Lentera Ilmu on July 17, 2019 until July 19, 2019. The subjects in this study were IV A classes totaling 30 students at SD IT Lentera Ilmu. Data collection using pretest and posttest data as well as the questionnaire method to determine the assessment of e-book nuanced Islamic on understanding the concept of elementary level conducted by material validators, media and Islamic fiqh. Based on the results of the research from the pretest and posttest data it can be concluded that H0 is rejected and H1 is accepted. Then there are differences in learning outcomes using mathematic e-books with Islamic nuances towards understanding student concepts. And the mathematic e-book with Islamic nuance meets the criteria effectively used in learning based on the test of student learning outcomes with a percentage of 67% which is included in the criteria of good.